فاعلية استراتيجية مقترحة قائمة على التعلم المنظم ذاتيا في تنمية مهارات البحث العلمي والاتجاه نحوه والمعتقدات حول مهنة التدريس لدى طلاب الجامعة - الشافعي، جيهان أحمد محمود (جامعة عين شمس - كلية التربية - مركز تطوير التعليم الجامعي, 2024)
هدف البحث الحالي إلى قياس فاعلية استراتيجية مقترحة قائمة على التعلم المنظم ذاتيا في تنمية مهارات البحث العلمي، والاتجاه نحوه والمعتقدات حول مهنة التدريس، لدى طلاب الجامعة، هذا وقد تم استخدام المنهج التجريبي ذي التصميم شبه التجريبي للمجموعة التجريبية الواحدة (المصنفة إلى أربع مجموعات تجريبية وفقا لمتغيري النوع والتخصص) وللإجابة عن أسئلة البحث؛ تم استخدام ثلاثة أدوات: أولها: بطاقة معايير مهارات البحث العلمي، وثانيها: مقياس اتجاهات الطلاب/ المعلمين نحوه، وثالثها: مقياس المعتقدات حول مهنة التدريس، وقد أسفرت النتائج عن التوصل إلى التصور للاستراتيجية المقترحة القائمة على التعلم المنظم ذاتيا، وإثبات فاعليتها، وحجم أثرها الكبير في تنمية كل من: مهارات البحث العلمي، والاتجاه نحوه، ومعتقدات الطلاب المعلمين نحو مهنة التدريس. كما أسفرت النتائج عن وجود فرق دال إحصائيا بين متوسطات معدل الكسب الفعلي لدرجات الطلاب/ المعلمين في مهارات البحث العلمي في التطبيق البعدي، لصالح ذوي التخصصات العلمية، بينما لا توجد فروق دالة إحصائيا بين متوسطات درجات الطلاب/ المعلمين في مهارات البحث العلمي ترجع إلى نوع الطلاب، كما لا توجد فروق دالة إحصائيا بين متوسطات درجات الطلاب/ المعلمين في التطبيق البعدي لمقياسي الاتجاه نحو البحث العلمي والمعتقدات حول مهنة التدريس، ترجع للتخصص أو نوع الطلاب، عدا البعد الثاني في مقياس الاتجاه نحو البحث العلمي (الاهتمام بتطبيقه في الحياة)، حيث كان الفرق لصالح الطلبة الذكور؛ لذا فأوصى البحث الحالي بتطبيق الاستراتيجية المقترحة والاهتمام بتدريب الطلاب والأكاديميين عليها؛ لما حققته من نتائج إيجابية، والاهتمام بتنمية مهارات التعلم المنظم ذاتيا بصفة عامة لدى الطلاب، ولأصحاب التخصصات الأدبية على وجه الخصوص. The aim of the current research is to investigate the effectiveness of a proposed strategy based on self-regulated learning in developing scientific research skills, attitudes towards it, and beliefs about the teaching profession, among university students. An experimental approach with a quasi-experimental design was used for one experimental group (classified into four experimental groups According to the variables of type and specialization) To answer the research questions, three tools were used: the first was the scientific research skills standards card, the second was a scale of students'/teachers' attitudes towards it, and the third was a scale of beliefs about the teaching profession. The results are summarized in: reaching to Build the proposed strategy based on self-regulated learning, Proving its effectiveness and the extent of its significant impact on the development of: scientific research skills, attitudes towards it, and student teachers' beliefs towards the teaching profession. The results also revealed that there was a statistically significant difference between the averages of the actual gain rate for the scores of students/teachers in scientific research skills in the post-application, in favor of those with scientific specializations, while there were no statistically significant differences between the averages of the scores of students/teachers in scientific research skills due to the type of students. There are also no statistically significant differences between the average scores of students/teachers in the post-application of the two scales of attitude towards scientific research and beliefs about the teaching profession, due to specialization or type of students, except for the second dimension in the scale of attitude towards scientific research (interest in applying it in life), where it was The difference is in favor of male students, so the current research recommended applying the proposed strategy and paying attention to training students and academics on it. Because of the positive results it has achieved, and the interest in developing self-regulated learning skills in general among students, and those with literary majors in particular.
Keywords: الاستراتيجيات التعليمية -- التعلم الذاتي -- المهارات البحثية -- مهنة التدريس -- طلبة الجامعات